Emerging trends in nanotechnologies for vitamin delivery: Innovation and future prospects - Md. Sumon Miah; Md. Waziur Rahman Chy; Tanvir Ahmed; Mahjabin Suchi; Md. Awwal Muhtady; Shah Nizam Uddin Ahmad; Mohammad Afzal Hossain (Nano Trends)
Nanotechnology has emerged as a cutting-edge approach to improving Vitamin Delivery systems, addressing critical challenges such as poor solubility, instability, and limited bioavailability. Conventional Vitamin Formulations are often challenged with rapid degradation and inefficient absorption, reducing their effectiveness. Integrating nanocarriers - including polymeric nanoparticles, lipid-based nanoparticles, metal-based systems, liposomes, and nano-emulsions - has demonstrated significant potential in enhancing vitamin stability and controlled release, optimizing nutrient uptake in the body. This review explores the diverse applications of nanotechnology in Vitamin Delivery, emphasizing the advantages of various nanocarrier systems. It discusses how nanoscale delivery platforms improve vitamin protection, solubility, and absorption, potentially leading to more effective supplementation strategies. Additionally, key challenges hindering the large-scale adoption of these technologies are examined, including concerns related to toxicity, regulatory uncertainties, and economic feasibility. The need for standardized safety assessments and well-defined regulatory frameworks remains a major hurdle in translating laboratory research into commercially viable products.